Servicios ofrecidos por los prestadores de alojamiento universitario en las localidades de Chapinero, usaquen y la candelaria (2022)
Bogotá is one of the most representative cities of our country, since it stands out as a cultural, economic and recreational center in Colombia and Latin America, which attracts students looking for an educational experience and an infinity of activities to do, places to know; museums, theaters, libraries and other entertainment areas.